1977
DOI: 10.1007/bf01434071
|View full text |Cite
|
Sign up to set email alerts
|

The?-decay of100Y: Discovery of a very low lying 0+ state in100Zr

Abstract: The /?-decay of lOOy has been investigated at the gas filled recoil separator JOSEF by means of 7-ray and conversion electron spectroscopy. Two B-decay modes, of half lives 0.94 + 0.03 s and 0.55 _+ 0.15 s, have been observed. Using XV-, Xce-, V7-and 7ce-coincidences the level scheme of ~~176 has been constructed. An excited 0~-state at 331.3 keV has been discovered in this nucleus. The/~-decay from the 0.55 s decay mode in 10oy shows a strong preference for the ground state compared to the 0~-state in ~~176 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…In some particular cases, half-lives from β-decay isomers were found in the literature. In particular, Khan et al [59] reported two different half-lives for 100 Y 61 , presumably from low-and high-spin β-decaying isomers. The T 1/2 measured in the present experiment for this nucleus is compared in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In some particular cases, half-lives from β-decay isomers were found in the literature. In particular, Khan et al [59] reported two different half-lives for 100 Y 61 , presumably from low-and high-spin β-decaying isomers. The T 1/2 measured in the present experiment for this nucleus is compared in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity decrease fits to a B-half life of 1.00_+0.13s [25]. Hence a/s-decaying isomeric state must exist in 99y.…”
Section: Isomeric: State In 99ymentioning
confidence: 91%
“…Experimental [1][2][3][4] as well as theoretical [5][6][7] studies of the region of neutron-rich nuclei around A = 100 have established the fact that a few isotopic chains (i.e. St, Zr, Mo) exhibit a rapid transition from vibrational to rotational structure when the number of neutrons is increased beyond N= 60.…”
Section: Introductionmentioning
confidence: 98%